An optimal replacement policy for a series repairable system with two dissimilar components based on downtime - Qinhui Fu; Xianyun Meng (2011 International Conference on Multimedia Technology, 2011)
In this paper, a geometric process repair model for a two-dissimilar-identical component series repairable system with a repairman is proposed. Assume that the component after repair is not "as good as new", and a repair can be delayed with a probability of 1-p i ,(i=1,2) , by using geometric process and renewal theory, we consider a replacement policy (M,N)based respectively on the number of failures of component 1, component 2. The expression of the long run average cost and the expected downtime per unit time are derived. Meanwhile, the replacement policy model is presented with minimizing the expected downtime rate subject to an appropriate cost rate. Finally, an appropriate numerical example is given to approve the rationality of the new model.